Evaluation of the causes of error in the mcd45 burned-area product for the savannas of northern south america (2012)
Forest fires contribute to deforestation and have been considered a significant source of CO2 emissions. There are global maps that estimate the area affected by fire using the reflectance variation of the surface. In this study we evaluated the reliability and the causes of error of the MCD45 Burned Area Product, by applying the confusion matrix method to the Orinoco River basin. This basin is located in the northern zone of South America, and consists mainly of savanna ecosystemst. For the evaluation we used as reference data five pairs of Landsat images, covering 165,000 km2. The Burned Area Product estimated a burned area of 7,576.43 km2, which is lower than the area of 12,100.16 km2 found with Landsat images, leading to an overall underestimation. The causes of error are associated to the spatial resolution of the map, and to some structures of the algorithm that generates the map.